6x-3y+18=0

Simple and best practice solution for 6x-3y+18=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-3y+18=0 equation:


Simplifying
6x + -3y + 18 = 0

Reorder the terms:
18 + 6x + -3y = 0

Solving
18 + 6x + -3y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + 6x + -18 + -3y = 0 + -18

Reorder the terms:
18 + -18 + 6x + -3y = 0 + -18

Combine like terms: 18 + -18 = 0
0 + 6x + -3y = 0 + -18
6x + -3y = 0 + -18

Combine like terms: 0 + -18 = -18
6x + -3y = -18

Add '3y' to each side of the equation.
6x + -3y + 3y = -18 + 3y

Combine like terms: -3y + 3y = 0
6x + 0 = -18 + 3y
6x = -18 + 3y

Divide each side by '6'.
x = -3 + 0.5y

Simplifying
x = -3 + 0.5y

See similar equations:

| 6-x=-10 | | 5x+16y-12z=230 | | 2y-4x-12=0 | | 10x+24y=123 | | 9x+11=7x+1 | | x(x-3)(x-5)=0 | | -1.9=-11.78 | | 6x-6-6=2x-4+4x | | -4.2+5x=3 | | 6n+13=67 | | n^2-2n=-1 | | 2-5=4-x | | -10t+25+3t=2t-9 | | 95-5x=13x+19 | | 2-4=4-x | | 124-5x=40x+24 | | 2x(x+21)=756 | | 10x+30=10x+30 | | 6(x-2)+5=-13 | | 3a+5=7 | | -8y-13=4y+11 | | 3(2x+18)-4x-22=7x-18 | | (2x+14)(x+14)=952 | | 5(2a-1)=9(a-5) | | -4y+4=-6y-6 | | 12x+6=54 | | 144-3x=5x-24 | | 9=5(2c-5) | | 2(x^2+14x-378)=0 | | 5x+2y=52 | | 9m+9=8m+5 | | -3=4N-(7) |

Equations solver categories